Services of the Worship House of the Padepokan Dhammadipa Buddhist House of Worship for People with Disabilities - M. Ilham Nurhakim; Yayuk Yuliati; Fadillah Putra (Department of Special Education, 2022)
Attention to disability is still not evenly distributed. The right to practice worship was not under the needs of disabilities. This study assesses the services of the Padepokan Dhammadipa Arama Buddhist Vihara in Batu City for disabilities. The theory used in this study uses the theory of planned behavior and the theory of social action. Data were collected through in-depth interviews and observations. The data were tested for validity using data triangulation and analyzed using pattern matching, explanations, and time series analysis. The results showed that Vihara administrators did not discriminate against disabilities because the basic principle of Buddhists is compassion. Services that have been provided are in the form of physical services like guardrails and non-physical services like assistance for the mobilization. The existence of this service is influenced by the understanding of disabilities and the urgency of providing services for disabilities. Efforts that continue to be made include innovating in the form of development systems and concepts, adding facilities and infrastructure at the Vihara, and increasing the participation of Buddhists in providing input and suggestions regarding disability services in places of worship. The hope is the existence of physical disability services will increase the security and comfort of people with disabilities in carrying out worship like normal people.